Effect of general boundary and coupling conditions on the vibration and power flow characteristics of a coupled H-shaped three-plate structure. (October 2019) - Mahapatra, Kavikant; Panigrahi, SK
Coupled H-shaped three-plate structures are extensively used as support platforms for machinery structures in engineering applications. These structures are constructed with various types of real engineering boundaries and coupling mechanisms. This investigation presents a numerical analysis of the effect of finitely varying boundary and coupling conditions on the vibration and power flow characteristics of a coupled H-shaped three-plate system. Modified Fourier series approximation of out-of-plane and in-plane displacement along with the Rayleigh–Ritz energy minimising procedure has been utilised for theoretical analysis, and different cases of variation of boundary and coupling spring stiffnesses have been taken to numerically analyse its effect on the vibration and power flow characteristics of the plate system. The numerical results indicate the presence of three different zones of finite coupling stiffness combinations at the coupled junction wherein the natural frequency and mode shapes undergo a major alteration. The decay or amplification of power flow characteristics across the plate junctions has been found to be highly dependent on the coupling stiffness values at the junctions. The consideration of general boundaries and coupling conditions in coupled plate systems is an essential design necessity for accurate prediction of the dynamic behaviour of coupled plate structures as their finite variations greatly influence the vibration and power flow characteristics of the coupled system.